A case report on transient cardiomyopathy with cytokine storm in SARS-CoV-2. Issue 2 (29th December 2020) - Tarun, Tushar; Kumar, Senthil; Johnson, Jeremy; Chockalingam, Anand
Abstract: Background: Cardiac manifestations during Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) pandemic have included acute coronary syndrome, arrhythmias, myocarditis, and stress cardiomyopathy. However, the combination of cardiomyopathy and negative cardiac biomarkers has not yet been reported. Case summary: A 49-year-old man admitted for respiratory failure secondary to SARS-CoV-2 developed new-onset cardiomyopathy with negative cardiac biomarkers. Left ventricular ejection fraction and strain improved 7 days after the initial echocardiogram, after administration of Tocilizumab, coinciding with clinical recovery, and improvement in inflammatory markers. Discussion: As experience of cardiovascular manifestations of SARS-CoV-2 increases, more patients will likely present with cardiovascular manifestations; the recognition and proper management of these may improve patient outcomes.